AI-dependency pada Mahasiswa: Ancaman Baru bagi Kemampuan Berpikir Kritis dan Peran Pendidikan Tinggi - Siska Putri Ayu (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2026)
The rapid integration of Artificial Intelligence (AI) tools in higher education has benefits but also introduced new challenges, particularly the phenomenon of AI-dependency students’ excessive reliance on AI for academic tasks. This conceptual article Aims to examine the psychological mechanisms underlying AI-dependency, its implications for cognitive processing and critical thinking skills, and the potential risks it poses to academic integrity and autonomous learning. This study employs a conceptual literature review, drawing on relevant scholarly articles retrieved from major academic databases such as Scopus, Web of Science, and Google Scholar, with a focus on publications related to AI use in education, cognitive processes, and critical thinking. The literature was synthesized using a narrative–thematic analysis to identify key patterns, concepts, and institutional responses to AI-dependency. The article concludes that higher education institutions play a strategic role in mitigating AI-dependency through curriculum design, critical AI literacy development, assessment practices emphasizing higher-order thinking skills, and academic support systems. These institutional interventions are essential to ensure that AI functions as a cognitive support tool rather than a substitute for critical thinking.